2010
DOI: 10.1308/003588410x12628812459779
|View full text |Cite
|
Sign up to set email alerts
|

Consenting for pelvic nerve injury in colorectal surgery: need to address age and gender bias

Abstract: The risk of pelvic nerve injury is not frequently stated, which is more common in women and the elderly. Overall, only 36% of patients were consented for pelvic nerve injury, while only 5% of women were consented. Is this professional discretion, or evidence that surgeons are not being assiduous enough when obtaining consent, which may leave them vulnerable to medicolegal claims? Introduction of procedure-specific consent forms would be a method to address this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Nesargikar et al [15] found that in colorectal surgery, only 36% were consented for pelvic nerve injury, with less patients consented for this in the over 70 years of age group compared to the under 50 years of age group, even though there is a bias for the elderly and women to be affected. Hoosein et al [16] retrospectively analysed the notes of patients who underwent open inguinal hernia repairs and found that many serious complications were not adequately recorded, irrespective of the seniority of the person consenting the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Nesargikar et al [15] found that in colorectal surgery, only 36% were consented for pelvic nerve injury, with less patients consented for this in the over 70 years of age group compared to the under 50 years of age group, even though there is a bias for the elderly and women to be affected. Hoosein et al [16] retrospectively analysed the notes of patients who underwent open inguinal hernia repairs and found that many serious complications were not adequately recorded, irrespective of the seniority of the person consenting the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of the anatomical integrity of the mesorectum is a major factor in long-term survival and rate of local recurrence after TME. Moreover, the challenge in cross-stapling in a narrow pelvis and efforts to preserve the anal sphincter in very low tumors could lead to major morbidity, including anastomotic failure and pelvic nerve injury [12][13][14][15]. NOTESinspired techniques with a ''down-to-up'' transanal approach to TME have been reported in order to overcome these risks in patients with rectal cancer [7,8,[16][17][18][19][20].…”
mentioning
confidence: 99%
“…15 Good surgical practice states that patients have a right to information about their condition and available treatments, including complications associated with treatment, to allow them to form a balanced and considered decision. 15 Patients often find the discussion of sexual issues difficult and some may believe that their doctors will dismiss their ED as unimportant. In a survey by Perelman et al, 33 and 38 per cent of men found speaking about their ED impossible and embarrassing to discuss with their doctors, respectively.…”
Section: Importance Of Counsellingmentioning
confidence: 99%